2009
DOI: 10.1016/j.jacc.2009.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Combined Increased Chemosensitivity to Hypoxia and Hypercapnia as a Prognosticator in Heart Failure

Abstract: Increased chemosensitivity to both hypoxia and hypercapnia, eliciting neurohormonal derangement, ventilation instability, and ventricular arrhythmias, is a very serious adverse prognostic marker in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
143
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 25 publications
(28 reference statements)
3
143
1
6
Order By: Relevance
“…In patients with heart failure, increased chemosensitivity and consequent ventilatory oscillations are harbingers of the neurohumoral derangement that ultimately predisposes to mortality (42,43). On this basis, a simple means to quantify reduced stability, as distinct from increased biological noise, may have clinical usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with heart failure, increased chemosensitivity and consequent ventilatory oscillations are harbingers of the neurohumoral derangement that ultimately predisposes to mortality (42,43). On this basis, a simple means to quantify reduced stability, as distinct from increased biological noise, may have clinical usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic nerve system activation is an invariant response to pathological respiratory chemoreflex activation [25], and sustained Fig. 1 The left plot shows the negative association between LTL and e-LFCNB, and the right plot shows the negative association between e-LFCNB and HFC sympathoexcitation [26] may be a plausible explanation for the rise in e-LFCNB during sleep. Another plausible explanation of the association may be the sleep fragmentation itself, which can induce hypertension, insulin resistance and metabolic dysregulation [24,[27][28][29].…”
Section: Discussionmentioning
confidence: 95%
“…Enhanced CO 2 chemosensitivity occurs in HF 36 and correlates with sympathetic activation 37 and natriuretic peptide elevation 38,39 as well as HF mortality. 38 Augmented chemosensitivity also promotes hyperventilation with reduction of CO 2 concentration below the apneic threshold, thereby causing compensatory and cyclic hypopnea or apnea characteristic of CSA.…”
Section: Lavi and Co 2 Chemosensitivitymentioning
confidence: 99%
“…38 Augmented chemosensitivity also promotes hyperventilation with reduction of CO 2 concentration below the apneic threshold, thereby causing compensatory and cyclic hypopnea or apnea characteristic of CSA. 25,26,40,41 Consistent with prior studies, 25,26,40 we observed that CO 2 chemosensitivity is augmented in patients with HF with CSA.…”
Section: Lavi and Co 2 Chemosensitivitymentioning
confidence: 99%